2018
DOI: 10.1007/s11120-018-0580-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the photosynthetic apparatus and lipid droplet formation in Chlamydomonas reinhardtii under iron deficiency

Abstract: The unicellular photosynthetic alga Chlamydomonas reinhardtii was propagated in iron deficiency medium and patterns of growth, photosynthetic efficiency, lipid accumulation, as well as the expression of lipid biosynthetic and photosynthesis-related proteins were analysed and compared with iron-sufficient growth conditions. As expected, the photosynthetic rate was reduced (maximally after 4 days of growth) as a result of increased non-photochemical quenching (NPQ). Surprisingly, the stress-response protein LHCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 59 publications
3
18
0
Order By: Relevance
“…Therefore, this organism was selected to investigate the influence of two-stage iron starvation on TAG accumulation. We recently reported the effect of iron stress conditions on cellular biomass and the proteins involved in lipid biosynthesis in C. reinhardtii (Devadasu et al, 2019). In the present study, we examined the effect of two-stage iron starvation on growth rate and lipid production in this species.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, this organism was selected to investigate the influence of two-stage iron starvation on TAG accumulation. We recently reported the effect of iron stress conditions on cellular biomass and the proteins involved in lipid biosynthesis in C. reinhardtii (Devadasu et al, 2019). In the present study, we examined the effect of two-stage iron starvation on growth rate and lipid production in this species.…”
Section: Introductionmentioning
confidence: 91%
“…Two major obstacles to the production of biodiesel from microalgae is (1) poor growth in culture leading to low cell density with low cellular lipid content and (2) stress conditions promotes neutral lipid content while decreasing growth (James et al, 2011). Previous reports show that total lipid levels in C. reinhardtii cells increased dramatically by iron starvation (Urzica et al, 2013;Devadasu et al, 2019). Since continuous exposure of cells to iron limitation causes plastid and ER stress and is highly likely to result in the degradation of cells (apoptosis).…”
Section: Influence Of Iron Deficiency On the Growth Of Chlamydomonas Reinhardtiimentioning
confidence: 99%
“…In vascular plants, a drastic decrease in MGDG content occurs during freezing or ozone treatment (Li et al, 2008). Our group recently reported that TAG accumulation originated from the degradation of MGDG under Fe deficiency from C. reinhardtii (Devadasu et al, 2019).…”
Section: Protein Analysis By Immunoblotmentioning
confidence: 99%
“…Results analysis showed that the Fv/Fm ratio was significantly affected by Fe deficiency treatment, especially in the sensitive genotypes TN1.11 and TN6.18. Iron deficiency leads to a significant decrease of net CO 2 , assimilation rate (A) and stomatal conductance (Ci) (Devadasu et al, ; Wang et al, ). Several authors indicated that iron deficiency has generally a negative effect on the photosynthetic mechanism and specifically on net photosynthetic rate and the gas exchange provided by the stomata (Morales, Pavlovič, Abadía, & Abadía, ).…”
Section: Discussionmentioning
confidence: 99%